Elder neglect in civil versus criminal court: legal decision-making in cases of overmedication - Le Grand, Alexis M. (Psychology, crime & law, 2021)
Despite recent increases in reported cases of elder overmedication, there is little research investigating the perception of elder overmedication in the courtroom. Male and female participants (N = 169, 95 females) read an overmedication civil or criminal trial summary involving a male or female victim. Participants were more likely to make pro-victim trial judgments (e.g. Plaintiff decision) when the trial was presented in civil court compared to criminal court. Additionally, victim and defendant credibility mediated the relationship between trial type and outcome. Civil trials led to enhanced victim credibility and weakened defendant credibility, which then led to more pro-victim trial judgments. Finally, participants who had positive experiences with elders exhibited greater sympathy for the victim and perceived them as more credible. We discuss these results in terms of the legal implications of bringing cases of elder overmedication to court.